2015
DOI: 10.1002/2015wr017125
|View full text |Cite
|
Sign up to set email alerts
|

Integrating social and physical sciences in water management

Abstract: Water management has always required more than physical science. This paper reviews the accomplishments of integrating social with physical sciences for water management in the last 50 years. Particular successes are highlighted to illustrate how fundamentals from both physical science and social science have been brought together to improve the performance of water management systems. Some forward-looking lessons for managing practical and academic interdisciplinary research for water management are also prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 106 publications
(124 reference statements)
1
51
0
1
Order By: Relevance
“…If drought frequency increases 30 years after a project was built, a new operating paradigm is needed. This has been supported by studies that have shown that there is a decrease in performance of hydropower systems if management is rigid and does not adapt to changing conditions (Mehta et al, 2011;Perez-Diaz and Wilhelmi, 2010;Minville et al, 2009Minville et al, , 2010aSchaefli et al, 2007;Robinson, 1997 (Lund, 2015;Milly et al, 2008;Oki and Kanae, 2006). This transfer can be accomplished by boundary organizations 4 , which can bridge science and practice by translating projections in a way that can inform decision-making (Gordon et al, 2016;Miller et al, 2001;Cash et al, 2001;Lowrey et al, 2009).…”
Section: Create Structural and Management Adaptations For Hydropower mentioning
confidence: 75%
“…If drought frequency increases 30 years after a project was built, a new operating paradigm is needed. This has been supported by studies that have shown that there is a decrease in performance of hydropower systems if management is rigid and does not adapt to changing conditions (Mehta et al, 2011;Perez-Diaz and Wilhelmi, 2010;Minville et al, 2009Minville et al, , 2010aSchaefli et al, 2007;Robinson, 1997 (Lund, 2015;Milly et al, 2008;Oki and Kanae, 2006). This transfer can be accomplished by boundary organizations 4 , which can bridge science and practice by translating projections in a way that can inform decision-making (Gordon et al, 2016;Miller et al, 2001;Cash et al, 2001;Lowrey et al, 2009).…”
Section: Create Structural and Management Adaptations For Hydropower mentioning
confidence: 75%
“…To fill this gap, the aim of our PWR concept is to enable the integration of physical and social sciences in water-related research. This integration goes beyond the approach of natural and/or engineering scientists to apply practices and techniques from the social sciences as described in Lund [44]. We intend to engage the perspective of both sciences in a discourse on water-related issues where reciprocal learning is a key component.…”
Section: The Pluralistic Water Research (Pwr) Conceptmentioning
confidence: 99%
“…Thus, it reinforces the relevance of existing approaches that integrate social and physical sciences to solve water management problems, and the need to go further in that direction (Reuss, 2003;Lund, 2015).…”
Section: Concomitantly Societies Have Rising Expectations Regarding mentioning
confidence: 98%
“…(Wilby and Dessai, 2010;Mastrandrea et al, 2010;Ekström et al, 2013). Cela renforce ainsi la pertinence des approches existantes visant à intégrer les sciences naturelles et sociales pour résoudre les problèmes liés à la gestion de l'eau, et l'intérêt de poursuivre les recherches dans cette direction (Reuss, 2003;Lund, 2015). agricoles (Thivet and Fernandez, 2012), en passant par les possibilités de réformes au niveau institutionnel qui permettraient des changements dans l'organisation et les règles de gestion du bassin versant (Roggero, 2015).…”
Section:  Groundwater Measuresunclassified
See 1 more Smart Citation